Public administration reform in Ukraine in the context of decentralization - Michal Cirner; Nataliya Maradyk (Annales Scientia Politica, 2020)
The fundamental reform of public administration in Ukraine started after political changes in 2014. This process is connected with decentralization, which is to ensure the transfer of finances and political powers from the state administration to self-government. Ongoing municipal reform is needed to create a viable self-government in Ukraine. The article deals with examples of good and bad practice in the implementation of public administration reform in Ukraine.